The effects of late nitrogen in the yield and quality of milling wheat : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in Agronomy at Massey University - Millner, James (Massey University, 1992)
The quality of wheat milled to produce flour for leavened bread is related to its protein content. The presence of specific proteins in milling wheat gives dough its elastic properties and dertermines baking quality. Good quality wheat will produce loaves with high volumes and a fine crumb texture. It is known that wheat cultivars differ in their ability to produce good quality bread through differences in the composition of their protein. In cultivars of good quality, the greater the protein content, the better the quality of bread produced. The Manawatu Mills Limited, Palmerston North varies the price it pays for milling wheat according to cultivar and protein content. Premiums can be obtained by increasing grain protein content. This presents local wheat growers with the financial incentive to improve the yield and quality of their crops. To investigate the feasibility of using late applications of nitrogen fertiliser to increase the protein content and yield of milling wheat three trials were carried out at different sites during the spring and summer of 1989/90. These sites were at Kairanga, Almadale and Waituna West in the Manawatu region using the cultivar Rongotea. They were chosen to provide a range of environmental conditions, particularly temperature, over which to test the effect of nitrogen fertiliser on protein content. To achieve different temperature regimes, these sites are situated at low, medium and high altitude. It has been suggested that temperature over the grain-fill period can influence both protein content and composition of wheat, which in turn influences its ability to produce good quality bread. Four different rates of nitrogen fertiliser were applied just prior to the boot stage. These were 0, 20, 40 and 80 kg N/ha. There were significant differences in grain yield amongst sites with Kairanga achieving 6.4 tonnes/ha, Almadale 5.9 tonnes/ha and Waituna West 6.8 tonnes/ha. These yields were above the long term district average. Grain yield responded to late nitrogen at Kairanga and Waituna West. Yields increased from 6.1 to 6.9 tonnes/ha at Kairanga and from 6.4 to 7.2 tonnes/ha at Waituna West as application rates increased from zero to 80 kg N/ha. Any potential yield response at Almadale was suppressed due to an infection of the root rot fungus, 'take-all'. The yield response at Kairanga resulted from an increase in grain weights whereas at Waituna West it resulted from an increase in ear numbers at harvest. At both responsive sites late nitrogen delayed conopy senescence. Protein contents also varied significantly amongst sites and in response to the application of nitrogen fertiliser. Protein content (14% moisture basis) ranged from 8.87 to 10.87% at Kairanga, from 10.35 to 11.28% at Waituna West and from 12.97 to 13.69% at Almadale as application rates increased from zero to 80 kg N/ha. The differences in protein levels obtained from different sites resulted in a considerable variation in baking quality. Samples from eight plots from each site were sent to the Wheat Research Institute, Christchurch, for test baking. Average bake scores were 19 at Kairanga, 21 at Waituna West, and 26 at Almadale. There was a strong, positive relationship between bake score and grain protein content amongst these samples. A convenient measure of baking quality, the sodium dodecyl sulphate test, was used to estimate baking quality of each plot. This allowed the relationship between baking quality and grain protein content to be identified for each site. The relationship between protein and baking quality differed between sites, being much stronger at Kairanga than at Almadale and Waituna West. The relatively poor relationship between protein and baking quality at Waituna West and Almadale can be partly explained by the limited range of protein contents resulting from treatment effects, particularly at Almadale. There was evidence that site had influenced the relationship between protein content and baking quality. At Kairanga and Waituna West late applications of nitrogen fertiliser significantly increased both grain yield and protein content. The yield increases, combined with the price premiums for increased protein, meant that it would have been profitable to apply late nitrogen. At Almadale there was no yield response and the protein response was limited, making late applications of nitrogen uneconomic. Pest and disease pressure at Almadale reduced yield, contributing to grain protein content being above the point where premiums are available. It was concluded that it can be economically feasible to use late applications of nitrogen on crops which have a high potential yield. Factors limiting yield, such as pests, diseases and moisture stress, will limit any potential benefit.
Keywords: Wheat Yields; Wheat Fertilizers; Wheat -- Effect of nitrogen on; Crops and nitrogen